1997
DOI: 10.1177/002215549704500502
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Expression of SPARC inXenopusEmbryos Interferes with Tissue Morphogenesis: Identification of a Bioactive Sequence in the C-terminal EF Hand

Abstract: SUMMARY SPARC is a matricellular Ca 2 ϩ -binding glycoprotein that exhibits both counteradhesive and antiproliferative effects on cultured cells. It is secreted by cells of various tissues as a consequence of morphogenesis, response to injury, and cyclic renewal and/or repair. In an earlier study with Xenopus embryos we had shown a highly specific and regulated pattern of SPARC expression. We now show that ectopic expression of SPARC before its normal embryonic activation produces severe anomalies, some of whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 37 publications
(44 reference statements)
3
21
0
Order By: Relevance
“…Our laboratory and others have demonstrated that a mimetic peptide corresponding to the unique C-terminal disulfide bridge of EF-hand2 of SPARC (peptide 4.2) has potent anti-proliferative and counteradhesive activities, both in vitro and in vivo (Damjanovski et al 1997;Lane and Sage 1990). While other mimetic peptides corresponding to other domains of SPARC have biological activity in vitro, to date only peptide 4.2 has been shown to mimic these effects in vivo.…”
Section: Discussionmentioning
confidence: 98%
“…Our laboratory and others have demonstrated that a mimetic peptide corresponding to the unique C-terminal disulfide bridge of EF-hand2 of SPARC (peptide 4.2) has potent anti-proliferative and counteradhesive activities, both in vitro and in vivo (Damjanovski et al 1997;Lane and Sage 1990). While other mimetic peptides corresponding to other domains of SPARC have biological activity in vitro, to date only peptide 4.2 has been shown to mimic these effects in vivo.…”
Section: Discussionmentioning
confidence: 98%
“…Initial studies showed that SPARC was important in bone mineralization (18). Its role has been expanded to include tissue remodeling (19), endothelial cell migration (20,21), morphogenesis (19,22,23), and angiogenesis (24,25). SPARC has also been shown to have an antiproliferative effect on endothelial cells, mesangial cells, fibroblasts, and smooth muscle cells (26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…Developmental anomalies are induced by overexpressing or suppressing BM-40 in nematodes (19,20). Furthermore, microinjection of BM-40 RNA, protein, peptides, or antibodies against BM-40 interfere with Xenopus embryonic development (21,22). In contrast, deletion of the BM-40 gene in mice resulted in a relatively mild phenoptype, namely late onset cataract formation in the eye, whereas development proceeded normally (23,24).…”
mentioning
confidence: 99%